DETERMINANTS OF CUSTOMER`S SWITCHING INTENTION BASED ON EXPERIENCE AND SHARIA VALUE CONGRUITY - Muthmainah .; Muhammad Cholil (Universitas Mercu Buana, 2019)
This study aims to examine the factors that influence the customer`s switching intention, which are influenced by customer satisfaction and customer loyalty based on customer experience and congruity of sharia values. The sample size of 195 Sharia banks customers in Surakarta was taken using convenient sampling method. The research analysis used hierarchical regression with customer satisfaction as the independent variable, customer`s switching intention as the dependent variable and customer loyalty as a mediator variable. Besides that, it also uses customer experience and congrueity to sharia values as a moderator variable.Validity test, reliability test and classic assumption test have been carried out and the results meet the criteria according to the specified standards. The results of the research analysis show that customer satisfaction has a positive and significant effect on customer loyalty and has a negative effect on the customer`s switching intention and customer loyalty has a negative effect on customer`s switching intention. Customer loyalty partially mediates the effect of customer satisfaction on customer`s switching intention. However, the customer experience and congrueity sharia value does not strengthen or weaken the influence of customer satisfaction on customer loyalty and on customer`s switching intention and does not strengthen or weaken the influence of customer loyalty on customer`s switching intention. The theoretical and practical implications of the results of research that are considered relevant and need to be discussed can be used as orientation and direction for future research